A prospective study on the reciprocal influence between personality and attitudes, behaviors, and psychological characteristics salient in eating disorders in a sample of non-clinical adolescents. Issue 5 (19th October 2016) - De Caro, Elide Francesca; Di Blas, Lisa
ABSTRACT: Eating disorders are mosy likely to occur for the first time in adolescence. Delineating vulnerable personality profiles of unhealthy conditions helps prevent their onset and development. This study investigated a non-clinical sample of 142 adolescents and how some theoretically salient individual differences in personality contribute to predict changes in behaviors, attitudes, and psychological characteristics that are clinically significant in eating disorders (EDs). The results from cross-lagged pattern analyses supported the influence of depression, obsessiveness, and self-esteem in the trajectories favoring the development of psychological characteristics, such as ineffectiveness and interoceptive awareness, which are salient in the ED risk process. Results also confirmed that body mass index, perfectionism, and body dissatisfaction predict increases in dysfunctional concerns with weight control and food consumption. Empirical support for the impact of ED-relevant variables on personality self-views emerged as well. Trajectories linking EDs and personality in relation to sex differences and permeability to transitory psychological conditions in adolescence were also confirmed.